Strategi Komunikasi Program Corporate Social Responsibility Dalam Upaya Pemberdayaan Masyarakat Berkelanjutan - Inge Yulistia Dewi; Leila Mona Ganiem; Wawan Mulyana (Jurnal Visi Komunikasi, 2022)
This study aims to describe the communication strategy process of PT CAP's CSR program in community empowerment efforts in Cisiram Umbul Village. This research was conducted using a case study method and a qualitative approach. Data collection techniques in the form of interviews, observation and documentation study. The results showed that PT CAP had implemented the communication strategy process well, consisting of audience recognition, writing messages, forming methods, using media and selecting communicators. PT CAP's main empowerment activities consist of infrastructure improvements and development of woven bamboo products that have just reached capacitance. At the stage of a continuous community empowerment communication strategy, the activities carried out by PT CAP have not yet reached the termination stage because there are still obstacles in its implementation. However, PT CAP strives to continue to provide assistance and the program is still included in the annual activity plan. So that the resulting impact can be more optimal. Although it has not yet reached the termination stage, this program has an impact on the capacity of beneficiaries and also the respect of the community which has an impact on the company's positive image.